206. SINGLE-CELL RNA-SEQ ANALYSIS REVEALS ACCELERATED PROLIFERATION OF ESOPHAGEAL EPITHELIAL CELLS TO ELIMINATE NRF2-ACTIVATED CELLS. (24th September 2022) - Hirose, Wataru; Horiuchi, Makoto; Taniyama, Yusuke; Kamei, Takashi; Taguchi, Keiko; Yamamoto, Masayuki
Abstract: Nrf2 is a transcription factor that regulates cytoprotective genes in response to oxidative and electrophilic stresses. The activity of Nrf2 is mainly controlled by the protein degradation by Keap1, a ubiquitin E3 ligase adaptor. Most of esophageal squamous cell carcinomas (ESCC) exhibit constitutive Nrf2 activation by Keap1 dysfunction, resulting in the poor prognosis. However, it has not been clarified whether Nrf2 activation serves as the initiation in tumorigenesis of ESCC. We generated tamoxifen-inducible and squamous epithelium-specific Keap1 conditional knockout (Keap1-cKO) mice in which Nrf2 is activated segmentally in esophageal epithelium at the adult stage. Using Nqo1 that is a representative Nrf2 target gene as the marker of Nrf2-acitivated cells, we distinguished Keap1-deleted/Nrf2-activated cells and Nrf2-normal cells in immunohistochemical analysis and gene expression analysis. Single-cell RNA-seq (scRNA-seq) analysis was conducted to compare the gene expression of Nrf2-activated cells and Nrf2-normal cells from Keap1-cKO mice, and control cells from control mice. In Keap1-cKO mice, Nrf2-activated cells accounted for 35% at 1 week and 20% at 4 weeks after induction of Keap1 deletion. This decrease was based on observations that Nrf2-activated cells were eliminated from the epithelium due to the weakened attachment to the basement membrane. In contrast, DNA damage accumulated in Nrf2-normal cells neighboring Nrf2-activated cells. To clarify the cell fate in the esophagus, we compared Nrf2-normal cells to Nrf2-activated cells or control cells in scRNA-seq analysis. Gene sets of G2/M checkpoint and E2F targets, which regulate cell proliferation, were enriched in Nrf2-normal cells. Constitutive Nrf2 activation renders esophageal epithelial cells able to be selectively eliminated via cell competition. Nrf2-normal cells suffered from DNA damage, but not Nrf2-activated cells, have a potency to be an origin of ESCC. These results suggest that Nrf2 activation serves as a tumor promoter of ESCC, but not the initiator. We speculate that the other gene mutations such as Tp53 are needed for the initiation to form ESCC prior to Nrf2 activation.